Analysis of the Application of Financial Management and Supporting Factors to Business Development Opportunities in MSMEs during the Covid-19 Pandemic - Ricky Atmaja; Romulo Sinabutar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The prolonged Covid-19 pandemic has an impact on people's economic activities, one of which is affected by the drivers of Independent Small Medium Enterprises (MSMEs). This research aims to measure theapplication of financial management and several other factors to the development of MSMEs during the Covid-19 pandemic. The population of this study was respondents who had independent small medium-sized businesses with special toy sales products andsamples from 100 respondents were taken with a simple random sampling technique. The research method used is a quantitative descriptive method, a data collection technique with the dissemination of questionnaires, before the data is analyzed the research instruments are first carried out validation tests and classical assumption tests. The research hypothesis was tested partially and simultaneously with a 5% signification rate. The results showed that the implementation of financial management (X1) did not affect the development of MSMEs and purchasing power (X2) had a positiveimpact.